BLOCKCHAIN CONSENSUS FOR RESOURCES CONSTRAINT DEVICES: A HYBRID APPROACH USING PoA, DPoS AND THRESHOLD CRYPTOGRAPHY - Yusof, S.H.; Zahilah, R.; Othman, S.H. (Journal of Engineering and Technology (JET), 2024)
This research explores the development of a hybrid consensus algorithm that combines the benefits of Proof of Authority (PoA), Delegated Proof of Stake (DPoS), and threshold cryptography to create a secure, efficient, and scalable consensus mechanism for resource-constrained devices. The proposed algorithm addresses traditional consensus algorithms’ limitations in resource-constrained environments, where energy efficiency, security, and decentralisation are crucial. By leveraging the strengths of PoA, DPoS, and threshold cryptography, this hybrid approach is anticipated to provide a robust and adaptable consensus mechanism to support many applications in IoT, edge computing, and other resource-constrained domains. The research aims to investigate the feasibility, performance, and security of this hybrid consensus algorithm and its potential to enable secure, decentralised, and scalable blockchain-based systems for resource-constrained devices.